Effects of Conjugated Linoleic Acid Associated With Endurance Exercise on Muscle Fibres and Peroxisome Proliferator‐Activated Receptor γ Coactivator 1 α Isoforms. Issue 5 (21st September 2016) - Barone, Rosario; Sangiorgi, Claudia; Marino Gammazza, Antonella; D'Amico, Daniela; Salerno, Monica; Cappello, Francesco; Pomara, Cristoforo; Zummo, Giovanni; Farina, Felicia; Di Felice, Valentina; Macaluso, Filippo
Abstract : Conjugated linoleic acid (CLA) has been reported to improve muscle hypertrophy, steroidogenesis, physical activity, and endurance capacity in mice, although the molecular mechanisms of its actions are not completely understood. The aim of the present study was to identify whether CLA alters the expression of any of the peroxisome proliferator‐activated receptor γ coactivator 1α (PGC1α) isoforms, and to evaluate the possible existence of fibre‐type‐specific hypertrophy in the gastrocnemius and plantaris muscles. Mice were randomly assigned to one of four groups: placebo sedentary, CLA sedentary, placebo trained, or CLA trained. The CLA groups were gavaged with 35 μl per day of Tonalin® FFA 80 food supplement containing CLA throughout the 6‐week experimental period, whereas the placebo groups were gavaged with 35 μl sunflower oil each day. Each administered dose of CLA corresponded to approximately 0.7 g/kg or 0.5%, of the dietary daily intake. Trained groups ran 5 days per week on a Rota‐Rod for 6 weeks at increasing speeds and durations. Mice were sacrificed by cervical dislocation and hind limb posterior muscle groups were dissected and used for histological and molecular analyses. Endurance training stimulated mitochondrial biogenesis by PGC1α isoforms (tot, α1, α2, and α3) but CLA supplementation did not stimulate PGC1α isoforms or mitochondrial biogenesis in trained or sedentary mice. In the plantaris muscle, CLA supplementation induced a fibre‐type‐specific hypertrophy of type IIx muscle fibres, which was associated with increased capillary density and was different from the fibre‐type‐specific hypertrophy induced by endurance exercise (of types I and IIb muscle fibres). J. Cell. Physiol. 232: 1086–1094, 2017. © 2016 Wiley Periodicals, Inc. Abstract : CLA supplementation did not stimulate PGC1α isoforms or mitochondrial biogenesis in trained or sedentary mice. CLA supplementation induced a fibre‐type‐specific hypertrophy of type IIx muscle fibres.